The Long-term Effect of Dobutamine on Intrinsic Myocardial Function and Myocardial Injury in Septic Rats with Myocardial Dysfunction. Issue 4 (October 2021) - Tang, Xiangxu; Xu, Yaqian; Dai, Xiaomeng; Xing, Yun; Yang, Duomeng; Huang, Qingyang; Li, Hongmei; Lv, Xiuxiu; Wang, Yiyang; Lu, Daxiang; Wang, Huadong
Abstract : ABSTRACT: Dobutamine (DOB) is recommended as an inotrope for septic patients with low cardiac output, but its long-term impact on sepsis-induced cardiomyopathy remains unclear. This study investigated the long-term effect of DOB on septic myocardial dysfunction and injury. Rats were exposed to cecal ligation and puncture (CLP), the intrinsic myocardial function, other organ functions, hemodynamics, inflammatory response, serum myocardial injury biomarkers, myocardial apoptosis, and vascular permeability were determined. At 6 h after CLP, the left ventricular ±dP/dt were significantly depressed, cardiac tumor necrosis factor-α and vascular cell adhesion molecule-1 expression were increased, but not serum cardiac troponin I (cTnI), N-terminal pro-brain natriuretic peptide (NT-proBNP), heart-type fatty acid-binding protein (H-FABP), creatinine, and urea nitrogen concentrations in CLP group compared with controls. At 9 h after CLP, hepatic dysfunction was present in CLP rats compared with controls. At 6 h after CLP, DOB treatment did not affect hemodynamics, the left ventricular ±dP/dt, cytokine levels in serum and myocardium, as well as cardiomyocyte apoptosis and cardiac vascular hyperpermeability at 20 h after CLP. However, DOB (10.0 μg/kg) increased serum IL-10 level and improved survival in septic rats. These results indicate that the intrinsic myocardial depression occurs earlier than hepatic and renal dysfunction in sepsis and serum cTnI, NT-proBNP, and H-FABP are not suitable as early biomarkers for sepsis-induced myocardial dysfunction. Although DOB treatment (10.0 μg/kg) in the presence of myocardial dysfunction improves survival in septic rats, it neither improves myocardial function and hemodynamics nor attenuates myocardial injury at the later stage of sepsis.